Comparison of Student Activeness and Interest in Learning in Inquiry Learning and Problem Based Learning: Learning Studies in the New Normal Era - Maghfira Febriana (Indonesian Journal of Advanced Research, 2023)
The purpose of this study was to determine the differences in students' activeness and interest in learning in the new normal era using a blended learning system with inquiry learning models and problem based learning. This comparative research with quantitative analysis uses observation to determine the activeness of students and a questionnaire to determine differences in learning interest. The observation results show that the class that applies blended learning with problem based learning (class B) is more active and enthusiastic about participating in learning than the inquiry learning class (class A). The results of the quantitative analysis using the T-test show that there are differences in learning interest between classes that apply the inquiry learning model to problem based learning. The conclusion from the research is that learning in the new normal era with blended learning is more effective using the problem based learning model to make students active and there are differences in learning interest from students using inquiry learning models and problem based learning.